Внесок викладачів вишів Волині та Рівненщини в охорону культурної спадщини рідного краю (1950-ті - початок 1990-х рр.) - Муляр, Галина; Muliar, Halyna (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено пам’яткоохоронну діяльність ряду представників професорсько-викладацького складу окремих вищих навчальних закладів Волинської та Рівненської областей у 1950-х – на початку 1990-х рр. Сха¬рактеризовано їх роботу щодо виявлення, вивчення, збереження та популяризації історико-культурних пам’яток обох регіонів. Проаналізовано значення такої роботи для поповнення музейних фондів насамперед археологічними реліквіями. Звернено увагу на внесок викладачів у популяризацію архітектурних пам’яток, зокрема сакральних.

The article deals with the study of the work of a number of professors and educators of some higher educational institutions of Volyn and Rivne regions that was relevant to artifacts protection in the 1950s till the beginning of the 1990s. A special attention has been paid to the description of their work and to the fields of their activity that were connected with discoveries, studies, preservation and popularization of the historical cultural heritage of both regions. The importance of such work for the enlargement the museums’ funds with archeological relics has been analyzed. The contribution of the professors and educators into the popularization of the archeological artifacts and monuments especially sacred ones has been viewed as the one that needs further research and study.
The Contribution of Educators of the Volynian Higher Educational Institutions into the Protection of Cultural Heritage of the Native Land (1950s – Beginning of the 1990s)
Keywords: викладачі; Волинь; Ровенщина; охорона культурної спадщини; археологічна реліквія; архітектурна пам'ятка; educators and professors; Volyn; Rivne region; protection of cultural heritage; archeological relic; archeological artifacts and monuments